Seasonal Variations in Particulate Matter Concentrations and Risk Factors for Respiratory Symptoms Among Residents Near Dumpsites in Benin City, Nigeria - Aimuanmwosa Frank Eghomwanre; Faith Osayekemwen Edokpolo (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
Rapid urbanization in Nigeria has increased the number of open dumpsites and waste burning, which are significant sources of particulate matter (PM). This study investigated seasonal PM variations and respiratory risk factors near the Otofure dumpsite in Benin City. PM2.5 and PM10 levels were measured at the dumpsite and residential areas during the wet and dry seasons. A cross-sectional survey was also conducted with 204 residents to assess self-reported health symptoms and potential risk factors. The data were analysed using nonparametric tests and logistic regression. The PM concentrations at the dumpsite (62.5–121.4 μg/m3) consistently exceeded residential levels and WHO 24-hour guidelines. The dry season peaks reached 8 times (PM2.5) and 2 times (PM10) the recommended limits, with significantly higher median concentrations than those in the wet season (p<0.05). Prevalent symptoms included cough (44.1%), eye irritation (27.0%), and shortness of breath (25.5%). Waste collection was significantly associated with shortness of breath (aOR: 4.52) and skin rashes (aOR: 2.85). Residents living in the area for 5–9 years were 3.71 times more likely to report eye irritation than shorter-term residents were. The Otofure dumpsite is a major source of PM pollution, creating a disproportionate health burden and environmental injustice. Urgent interventions are needed, including the cessation of open burning, improved waste management, and community health education to protect vulnerable residents.